Evaluating Nepal’s Truth and Reconciliation Commission (The Journal of Nuwakot Adarsha Multiple Campus, 2025)
The Comprehensive Peace Agreement (CPA) was concluded between the Government of Nepal and the Nepal Communist Party of Maoists (CPN-M) in 2006. The management of combatants and the drafting of a new constitution have been accomplished. However, the conflict victims of grave human rights violations are still waiting for justice. The CPA clearly promises that the whereabouts of the disappeared person(s) will be identified within 35 days. The families of people subjected to enforced disappearance are still waiting for their beloved family members.This paper assesses the role of the Truth and Reconciliation Commission and the Commission of Enforced Disappearances in providing comprehensive justice to conflict victims. It will minutely investigate the three questions: What happened during the armed conflict? How was the mechanism designed to deal with grievances of the past? Why has it failed so far in providing justice to the victims?The research will generate information and evidence through the archives of published books, articles, and reports. The materials have been taken from both academic and non-academic sources. There has been consulted published stories, narratives, and data from commissions as well as from human rights organizations. The conflict victims are in a helpless situation, as they have lost their family members and also face several obstacles in property transfer. In addition, it is assumed that the legacies of violence will continue if they are not addressed.